REVIEW OF APAMARGA (ACHYRANTHES ASPERA LINN.) IN VEDIC VAANGMAYA & SAMHITA GRANTHS (International Journal of Ayurveda and Pharma Research, 2016)
Apamarga, a well known herb is found as a weed throughout India. It is important to note that number of herbs gradually increased from Rigveda to Atharvaveda. This very fact indicate towards metamorphosis of a system of medicine which was earlier based on Hymns (mantras) later accepted more and more interventions/ herbal drugs. This trend continued in Samhita period and reached its extreme during Nighantu period. Therefore it is necessary to know about the vedic herbs. Apamarga is one of them. In Atharvaveda it is said to be Kshetriya roga nasak and Yatudhan Krimi nasak. In Yajurveda it is said to be used for hawan purpose due to its Rakshoghna property. No other plant has got better water removing property than Apamarga. It has also got property like Kushthaghna, Paaproga nasak, Duhswapnanasana. Apamarga is considered as lord of all plants because it posses hundreds of properties and wipe away all the diseases. In different Ayurvedic treatise it is indicated in Arsha, Kushtha, Unmada, Apasmara, Ashmari, Hikka-Swaas, Vish Chikitsa etc. Traditionally each and every part of the plant is used in different diseases like dysentery, asthma, piles, stomatitis etc. It is also used as anti diabetic, anti inflammatory, abortifacient etc. The present article gives the literary information regarding the different uses of Apamarga in Vedic Vaangmaya and Samhita Granths.